Do minority leaders affect corporate practice? Analyzing the effect of leadership composition on governance and product development. (May 2015) - Cook, Alison; Glass, Christy
This study examines the effect of racial/ethnic minority CEOs and diverse corporate boards on corporate governance and product development. We test an author-constructed dataset of corporate practices, CEO race/ethnicity, and board racial/ethnic composition in Fortune 500 firms from 2001 to 2010. Findings suggest that diverse boards are positively associated with effective corporate governance practices and product development. Moreover, an interactive effect occurs between a diverse board and the race/ethnicity of the CEO in that corporate governance strengths and product innovation for the firm are increased when a White CEO operates with a diverse board. Thus, while promoting individual minority leaders is important, board diversity is paramount for achieving corporate benefits.